(untitled) (Journal of Applied Learning and Teaching, 2024)
Mooting (also referred to as “moot court”) is a type of mock courtroom exercise that takes place in many law schools. In 2018-19, for the purposes of completing a Professional Doctorate in Law at Northumbria University, I organised a series of moots among student research participants and interviewed them about their experience of mooting. The purpose of this was to understand, through the lens of experiential learning theory, from the perspective of the student participants, what is involved in preparing for, participating in, and receiving feedback after a moot; the differing perceptions of students involved in a moot experience, and to analyse the learning experience of the students taking part in the moots. This article is a summary of the research that I undertook, what I learned from it, and how the experience of that research can inform further development of teaching and learning.